2020
DOI: 10.3390/brainsci10100703
|View full text |Cite
|
Sign up to set email alerts
|

Nucleus Accumbens Functional Connectivity with the Frontoparietal Network Predicts Subsequent Change in Body Mass Index for American Children

Abstract: The epidemiological observation that NAc functional connectivity is associated with BMI changes in children is an extension of well-controlled laboratory studies that have established the role of the NAc in the brain reward processing. More research is needed on sex differences in the brain regions that contribute to childhood obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 90 publications
(168 reference statements)
0
3
0
Order By: Relevance
“…NAc regulates motivated behaviors and intake and seeking reward, and response to cues related to food and drugs [81][82][83][84][85] . The Adolescent Brain Cognitive Development study (ABCD) 89 and other studies [81][82][83][84][85] show that data suggests that NAc changes predict disorders related to the reward [88][89][90][91][92][93][94] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NAc regulates motivated behaviors and intake and seeking reward, and response to cues related to food and drugs [81][82][83][84][85] . The Adolescent Brain Cognitive Development study (ABCD) 89 and other studies [81][82][83][84][85] show that data suggests that NAc changes predict disorders related to the reward [88][89][90][91][92][93][94] .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, research has established a correlation between NAc modifications and shifts in motivated behaviors, encompassing the regulation and pursuit of cues, food, drugs, addiction, and obesity [81][82][83][84][85] . Insights from research both external [81][82][83][84][85] and internal to the Adolescent Brain Cognitive Development (ABCD) study suggest the potential of NAc alterations as predictive markers for reward-related disorders in the future [88][89][90][91][92][93][94] .…”
Section: Introductionmentioning
confidence: 99%
“…The authors discussed the results in the context of obesity and possibly unhealthy eating, although the percentage of obesity or presence of unhealthy eating could not be reported [122]. Another study of the same cohort of children evidenced that higher functional resting state connectivity between the nucleus accumbens and the frontoparietal network was predictive of BMI increase over time, although only for the female group [123]. In adolescents, one study in a community sample (n = 122) observed that those with BED symptoms (possibly a mixed sample sBED/BED), compared to those without, showed an increased reward-receipt response in the caudate in a reward-guessing task when money was won [95].…”
Section: Reward-based Deficitsmentioning
confidence: 99%